The media and the sayings about teachers in Brazil: an analysis of journalistic discourse - Silmara Dela Silva; Regiane Gomes dos Santos (Cadernos de Letras da UFF, 2018)
This article aims to analyze discursively circulating statements in the journalistic media, nowadays, in its processes of production of meanings for teachers in Brazil. Based on the theoretical-methodological principles of discourse analysis, the analyzes point out how, when saying about the (dis) valorization of the teachers, the media reiterates the bankruptcy of the public school system.